2019
DOI: 10.1371/journal.pone.0217922
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor and restriction spectrum imaging reflect different aspects of neurodegeneration in Parkinson’s disease

Abstract: To meet the need for Parkinson’s disease biomarkers and evidence for amount and distribution of pathological changes, MRI diffusion tensor imaging (DTI) has been explored in a number of previous studies. However, conflicting results warrant further investigations. As tissue microstructure, particularly of the grey matter, is heterogeneous, a more precise diffusion model may benefit tissue characterization. The purpose of this study was to analyze the diffusion-based imaging technique restriction spectrum imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…These pathological findings are in accordance with phenotypic progression in PD, as many nonmotor symptoms precede the motor features of PD (Marras & Chaudhuri, 2016). Therefore, demonstrating pontine damage in patients with PD would provide in vivo evidence for Braak's hypothesis, although there are conflicting reports (Blain et al., 2006; Hope et al., 2019; Surova et al., 2015; Taylor et al., 2018). The pons is also an important neuropathological substrate of RBD (Iranzo, 2018; Knudsen et al., 2018), and a few neuroimaging studies have reported gray matter volume reduction or altered DTI parameters in the pons (Hanyu et al., 2012; Scherfler et al., 2011; Unger et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These pathological findings are in accordance with phenotypic progression in PD, as many nonmotor symptoms precede the motor features of PD (Marras & Chaudhuri, 2016). Therefore, demonstrating pontine damage in patients with PD would provide in vivo evidence for Braak's hypothesis, although there are conflicting reports (Blain et al., 2006; Hope et al., 2019; Surova et al., 2015; Taylor et al., 2018). The pons is also an important neuropathological substrate of RBD (Iranzo, 2018; Knudsen et al., 2018), and a few neuroimaging studies have reported gray matter volume reduction or altered DTI parameters in the pons (Hanyu et al., 2012; Scherfler et al., 2011; Unger et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We selected 20 scalar metrics from the six models (DTI, DKI, NODDI, RSI, SMT mc, WMTI) based on recent studies (Benitez et al, 2018;De Santis et al, 2011;Hope et al, 2019;Jelescu et al, 2015;Kaden, Kelm, et al, 2016;Maximov et al, 2019;Pines et al, 2020). NODDI: ICVF (intracellular volume fraction), ISOVF (isotropic volume fraction), OD (oriental dispersion).…”
Section: Diffusion Mri Processingmentioning
confidence: 99%
“…Restriction spectrum imaging (RSI) (80,81) is a new diffusion model based on high angular resolution diffusion imaging (HARDI), acquired in multiple directions at different high b values. RSI highlights hindered and restricted diffusion in extracellular and intracellular compartments.…”
Section: Advanced Diffusion Approachesmentioning
confidence: 99%
“…With the development of several new metrics, RSI can now provide information about neurite density and orientation. Hope et al ( 81 ) were the first to compare RSI with DTI in patients with PD. They defined a cellularity index and a neurite density index.…”
Section: Diffusion Weighted Imagingmentioning
confidence: 99%